(untitled) (Bangladesh Journal of Medical Science, 2018)
Introduction: The aim of this study was to assess professors’ and students’ educational needs and implementation of serial workshops and then evaluate the effect of these educational workshops on the knowledge and practice of medical students. Method: Students’ educational needs and the clinical professors’opinion were used tocomplete the needs assessment process.120 Medical students participated in serial workshops. This program was applied to develop educational accountability program. In each workshop, students’ knowledge was evaluated by valid and reliable multiple-choice questions before andafterthe course. In some workshops, their performance was measured by the OSCE test.Descriptive analysisandpaired t- test were used to evaluate difference in students’ mean score. Finding: Results of before and after series of workshops in various areas revealed that workshop programs had a significant impact on the promotion of students’ knowledge (The mean score of students before and after workshops). Then,the evaluation of theirperformance through the OSCEtest was significant(P <0.05). Furthermore, students’ evaluation on workshops demonstrated that almost all of them were satisfied with the proportion of the content of the workshops, with the theme of the announced program, with the quantity of presented material in the workshop, withthe appropriateness of the content to future employment needs and the ability to create order in the meetings.According to professors’ opinion, number of errors in prescription, errors in radiography request and malpractice in resuscitation were decreased and students’ performance in clinical wards was approved. Conclusion: The results showed that training through workshops leads to increase the level of knowledge, function and satisfaction in the medical students. It is recommended that this method be used to improve the professional abilities of students based on educational needs. Application / Improvements: Looking ahead, we should consider strategies for leading changes in education and training. Purposeful teaching is the best way to develop accountability in medical education Bangladesh Journal of Medical Science Vol.17(1) 2018 p.78-83